Cultural variations in ethical leadership: Insights into governance, integrity, and organizational practices - Amran, Zakaria; Mohd Rashid, Ab Hamid; Imaduddin, Abidin (RSIS International, 2025)
The impact of cultural differences and ethical leadership on performance, governance, and organizational integrity is investigated in this study. A key element in establishing trust, influencing corporate culture, and raising employee engagement is ethical leadership. By using bibliometric analysis, the study highlights the significance of cultural circumstances in determining leadership effectiveness and finds trends and patterns in ethical leadership studies. In order to overcome obstacles and attain long-term success, it is crucial to match moral behavior with a variety of cultural standards. The study also looks at the expanding relationship between innovation, sustainability, and international cooperation and ethical leadership. These components are essential for tackling today’s governance issues and building resilience in heterogeneous companies. This paper also suggests directions for future research, emphasizing how ethical leadership may be integrated with environmental programs and technology breakthroughs to remain relevant in a changing global environment.